2019
DOI: 10.15294/komunitas.v11i2.18123
|View full text |Cite
|
Sign up to set email alerts
|

Affirmation of the Social Approach in the Case of Relocation of Community in Ciliwung Riverbank

Abstract: Urban development projects often lead to social contraction between the technical-physical approach and the socio-cultural approach. To explain the problem, this paper inspires the concepts of urban anthropology and socio-cultural development. The study was conducted in 2016-2017 in community located in Ciliwung riverbank, Jakarta. The methods used include in-depth interviews, participatory observations, and document analysis. The results of the study show that although river normalization projects and relocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…Working as fishermen, of course, they live by relying on sea products. This encourages and reinforces the fact that the work of a fisherman is very dependent on the sea and does not generate too much income (Mahyuni 2019); (Irwan, 2015); (Irwan et al, 2019). The work of a fisherman must have mental strength and seriousness and seriousness in action (Arifin 2015).…”
Section: Introductionmentioning
confidence: 86%
“…Working as fishermen, of course, they live by relying on sea products. This encourages and reinforces the fact that the work of a fisherman is very dependent on the sea and does not generate too much income (Mahyuni 2019); (Irwan, 2015); (Irwan et al, 2019). The work of a fisherman must have mental strength and seriousness and seriousness in action (Arifin 2015).…”
Section: Introductionmentioning
confidence: 86%
“…Researchers present data in the form of words or pictures. This qualitative research is not manipulated by the researcher, because this research is based on the facts found in the field (Agustini et al, 2020), (Irwan, 2015a), (Irwan et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Hubungan yang dibangun melalui media sosial terjalin seperti dunia nyata. Media sosial memudahkan untuk membangun hubungan yang kompleks (Irwan 2019).…”
Section: Konstruksi Media Sosial Dalam Menyebarluaskan Trend Thriftin...unclassified